Kultúrdiplomáciai közeledés Magyarország és Olaszország között : 1926-1928 - Hamerli, Petra (Közép-Európai Közlemények, 2016)
In my paper I present the cultural approach between Hungary and Italy between 1926 and 1928. After the first World War – regarding to Europe – Italy aimed to obtain political influence in the Danubian basin and in the Balkans, where it was obstacled by one of the successory States, the Kingdom of Serbs, Croats and Slovenes (Yugoslavia). In 1926 Italy determined itself to take steps for weakening the Yugoslavian State and it searched for allies. As Hungary, which lost two thirds of its territory after the war, was interested is weakening the sucessory States, too, Italy began to approach to it. The cultural diplomacy could be used to this as a measure, so the minister of cultural affairs in Hungary, Kuno Klebelsberg was invited to Italy „to make conferences on the Italian–Hungarian Cultural Relations during the history”. Really, Klebelsberg and the Italian politicians established the relations of the two States by making agreements on a strong cultural cooperation. These accord was followed by the prime minister István Bethlen’s visit in Rome, when the Italian–Hungarian Treaty of Friendship was signed.